2020
DOI: 10.1073/pnas.1918481117
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural evidence for self-replication of Alzheimer-associated Aβ42 amyloid along the sides of fibrils

Abstract: The nucleation of Alzheimer-associated Aβ peptide monomers can be catalyzed by preexisting Aβ fibrils. This leads to autocatalytic amplification of aggregate mass and underlies self-replication and generation of toxic oligomers associated with several neurodegenerative diseases. However, the nature of the interactions between the monomeric species and the fibrils during this key process, and indeed the ultrastructural localization of the interaction sites have remained elusive. Here we used NMR and opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 55 publications
3
50
0
Order By: Relevance
“…Oligomers have variously been dened in the literature as species having smaller size, lower growth rate, less ordered structure, distinct surface properties or higher toxicity compared to brils 8,11,12,[14][15][16][17][18][19] (Fig. 2).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Oligomers have variously been dened in the literature as species having smaller size, lower growth rate, less ordered structure, distinct surface properties or higher toxicity compared to brils 8,11,12,[14][15][16][17][18][19] (Fig. 2).…”
mentioning
confidence: 99%
“…The examples shown illustrate oligomers formed on fibril surfaces during the fibril assembly process (left) and end state fibrils (right) (images adapted from ref. 14), or using solid-state NMR, in which case oligomers produce less well-resolved spectra (left, adapted from ref. 15) than fibrils (right, adapted from ref.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This mechanism of secondary nucleation is thus most powerful and the driving force of fibril aggregation of Aβ 1‐42 at least under the conditions studied [28] . Only recently, ultrastructural evidence for the existence of time‐intermediate growing aggregates along the sides of fibrils was observed using cryo‐electron microscopy (EM) and special conditions [29] . The TERS studies strengthen these findings and further highlight that these surface‐attached entities are composed of anti‐parallel β‐sheet secondary structures as the primary seeds.…”
Section: Figurementioning
confidence: 96%
“…Immunogold electron microscopy showed that formation of Abeta fibrils in vitro was drastically delayed in the presence of recombinant Bri2 and proSP-C BRICHOS domains, likely due to the fact that BRICHOS domain binds to Abeta fibrils, shielding it from further surface nucleation ( Willander et al, 2012 ). More recently, cryo-EM studies showed that the process of Abeta fibrillation consisted of both formation of free floating protofibrils as well as fibrils with surface nucleation; in the presence of the BRICHOS domain, a higher number of free-floating Abeta protofibrils were found, while in its absence, secondary nucleation was favored ( Tornquist et al, 2020 ). This supports the idea that the possible mechanism of action is by reducing secondary nucleation rather than prevention of de novo fibril formation.…”
Section: The Brichos Domainmentioning
confidence: 99%